TIME-SCOPE STRUCTURE OF DRAMA OF HRYHIR LUZHNICKIY “SISTER-PORTRESS” - Vivcharyk, N. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article on the example of drama “Sestra - Vorotarka” it is analysed internal relations of religious dramaturgy of Grygir Luzhnytsky with a mystery genre, including with miracle. It is became clear, that artistic image of Bohomatir-Vorotarka comes forward author variation of myth of reincarnation or transformation. Attention appeal on combination sacral and common. Composition is analysed, time-scope model of work.